2017
DOI: 10.1002/hipo.22799
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic inhibition gates excitatory LTP in perirhinal cortex

Abstract: The perirhinal cortex (PRh) is a key region downstream of auditory cortex (ACx) that processes familiarity linked mnemonic signaling. In gerbils, ACx-driven EPSPs recorded in PRh neurons are largely shunted by GABAergic inhibition (Kotak et al. 2015). To determine whether inhibitory shunting prevents the induction of excitatory long-term potentiation (e-LTP), we stimulated ACx-recipient PRh in a brain slice preparation using theta burst stimulation (TBS). Under control conditions, without GABA blockers, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…These results are in line with ours reporting alterations of neural plasticity in the motor cortex in patients with MDD. These observations are also consistent with animal studies reporting that the iTBS-induced LTP mechanisms could be modulated by the administration of GABA antagonists (Kotak et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with ours reporting alterations of neural plasticity in the motor cortex in patients with MDD. These observations are also consistent with animal studies reporting that the iTBS-induced LTP mechanisms could be modulated by the administration of GABA antagonists (Kotak et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…However, Kotak, Mirallave, Mowery, and Sanes (2017) (Nishiyama et al, 2010). In summary, animal studies have provided evidence that LTP induction depends on blocking GABAergic inhibition via the GABA receptors (Grover & Yan, 1999;Kotak et al, 2017;Liu et al, 2014;Staubli et al, 1999;Steward et al, 1990) and that of LTD may also depend on modulation of GABA interneuronal activities (Kotak et al, 2017;Nishiyama et al, 2010). .…”
Section: Glutamatergic and Gabaergic Neurotransmissions And Tbs Effmentioning
confidence: 99%
“…The presynaptic changes in GABA release are involved in the TBS-induced potentiation of synaptic plasticity (Larson & Munkacsy, 2015). In fact, several animal studies have indicated that the blockade of GABAergic inhibition (e.g., via the GABA-A receptor or GABA-B receptor) plays a key role in LTP induction (Grover & Yan, 1999;Kotak, Mirallave, Mowery, & Sanes, 2017;Liu et al, 2014;Staubli, Scafidi, & Chun, 1999;Steward, Tomasulo, & Levy, 1990). This disinhibitory process involves presynaptic GABA autoreceptors that inhibit GABA release.…”
Section: Glutamatergic and Gabaergic Neurotransmissions And Tbs Effmentioning
confidence: 99%
See 2 more Smart Citations